IDEOLOGI GENDER DALAM NOVEL TUHAN IZINKAN AKU MENJADI PELACUR: KAJIAN STILISTIKA FEMINIS SARA MILLS - Nur Atimah; Saharudin; Muh. Khairussibyan (Jurnal PENEROKA, 2026)
This study aims to uncover forms of gender subordination ideology and female stereotypes through a Feminist Stylistics analysis in the novel Tuhan Izinkan Aku Menjadi Pelacur! (TIAMP) by Dahlan. Patriarchal social constructions are often reflected in everyday life and prevalent in society; in literary works, this can be explored through the language used to represent women. The focus of this study is on how language represents women throughout the novel's text, as well as the positive or negative values that emerge from it. The research employs a qualitative descriptive method with Sara Mills' Feminist Stylistics approach, through data collection techniques involving library research, reading, and note-taking. The data analyzed consist of words, phrases/sentences, and discourses found in the novel's text. The research findings at the word level include gender ideology categories of Naming and Androcentrism, and the Female Experience category: Euphemism and Taboo. Next, at the phrase/sentence level, gender ideology categories of Presupposition and Inference, and Metaphor and Simile were found. Finally, at the discourse level, forms of gender ideology in the categories of Character and Role, and Fragmentation were identified.The study also uncovers the intriguing finding that language participates in perpetuating stereotypes that harm women.